2010
DOI: 10.1292/jvms.09-0506
|View full text |Cite
|
Sign up to set email alerts
|

Canine Hippocampal Formation Composited into Three-Dimensional Structure Using MPRAGE

Abstract: ABSTRACT. This study was performed to anatomically illustrate the living canine hippocampal formation in three-dimensions (3D), and to evaluate its relationship to surrounding brain structures. Three normal beagle dogs were scanned on a MR scanner with inversion recovery segmented 3D gradient echo sequence (known as MP-RAGE: Magnetization Prepared Rapid Gradient Echo). The MRI data was manually segmented and reconstructed into a 3D model using the 3D slicer software tool. From the 3D model, the spatial relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The canine brain presents many similarities with the human brain in anatomical organization, architectural complexity, gene expression (Griffiths, Duncan, Mcculloch, & Harvey, 1981;Hemsley & Hopwood, 2010;Wenger et al, 1999), physiology (Jung et al, 2010), and agerelated alterations (Cummings et al, 1996;Yu et al, 2011). Recent histological, immunohistochemical, and ultrastructural evidence suggests that the canine brain highly represents the adult human neurogenic events (Fernandez-Flores et al, 2018;Walton, Parmentier, & Wolfe, 2013).…”
mentioning
confidence: 99%
“…The canine brain presents many similarities with the human brain in anatomical organization, architectural complexity, gene expression (Griffiths, Duncan, Mcculloch, & Harvey, 1981;Hemsley & Hopwood, 2010;Wenger et al, 1999), physiology (Jung et al, 2010), and agerelated alterations (Cummings et al, 1996;Yu et al, 2011). Recent histological, immunohistochemical, and ultrastructural evidence suggests that the canine brain highly represents the adult human neurogenic events (Fernandez-Flores et al, 2018;Walton, Parmentier, & Wolfe, 2013).…”
mentioning
confidence: 99%
“…41 On MRI, the canine dentate gyrus can be seen at the level of the HF head, using a high ield MRI unit and advanced MRI sequence (magnetisation prepared rapid acquisition gradient echo sequence). 50 In our study, linear measurements were obtained at the level of the HF body because HF identiication at this level was facilitated by the surrounding CSF. In fact with a low ield MRI unit, the boundaries of HF head would have not been distinguishable.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the whole HF atrophying with ageing, 30–33 46–49 it was found that dogs older than 13 years had significant neuronal loss (−30 per cent) in the hilus of the dentate gyrus compared to younger dogs 41 . On MRI, the canine dentate gyrus can be seen at the level of the HF head, using a high field MRI unit and advanced MRI sequence (magnetisation prepared rapid acquisition gradient echo sequence) 50 . In our study, linear measurements were obtained at the level of the HF body because HF identification at this level was facilitated by the surrounding CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Image quality and contrast between gray and white matter are superior with the 3D-MPRAGE sequence compared with the T1-weighted spin echo (SE) sequence. [14,15] In this study we could obtain contiguous thin-section (1 mm) images with readily acquired multiplanar reformations obviating additional images and could depict more focal lesions. The 3D-MPRAGE sequence had 228-256 slices of which 60 slices on average contained the pediatric HC in raw data in this study.…”
Section: Discussionmentioning
confidence: 99%